Friction and wear characteristics of furcraea foetida fiber-reinforced epoxy composites - Hussain, Haja Syed; Mohd Jamir, Mohd Ridzuan; Abdul Majid, Mohd Shukry; Sapuan, S. M.; Yudhanto, Ferriawan; Nugroho, Aris Widyo; Rani, Muhammad Faiz Hilmi (Wiley, 2023)
In the current study, the friction and wear properties of Furcraea foetida fiber‐reinforced epoxy composites were investigated. This study evaluated the effect of Furcraea foetida fiber content on the tribological behavior of composites. A water‐retting method was employed to extract the fibers, and resin transfer molding was used to fabricate the composites. The frictional force, coefficient of friction (COF), and wear rate were measured under dry test conditions and various applied loads (80, 100, 120, and 140 N). Microstructural analysis was conducted using scanning electron microscopy to investigate the surface morphology and wear mechanisms of the composites. The results revealed that the composite with 50 vol% of fibers exhibits the lowest frictional force and COF in both normal and parallel orientations with overall average COF of 0.43 in normal orientation and 0.42 in parallel orientation. Moreover, the composite with 60 vol% demonstrates the best wear resistance with an overall average specific wear rate of 2.1982 ×  in normal orientation and 4.3478 × () in parallel orientation. Overall, this study provides valuable insights into the tribological behavior of Furcraea foetida fiber‐reinforced epoxy composites and identifies the optimal volume fractions for improved friction and wear performance.